A comparative study of Mencius's thoughts through human nature and harmony - Meng Xiaohong; Yunrui Zhong (Trans/Form/Ação)
This article focuses on Mencius' concepts of human nature and harmony, aiming to explore the intrinsic connection between the two and their implications for contemporary ethics, morality and social harmony. This article first provides a detailed analysis of Mencius' theory of human nature, pointing out that Mencius' "theory of good nature" emphasizes the human beings’ innate goodness. Then, using cross-cultural comparison methods, the similarities and differences between Mencius and Machiavelli in ethical concepts, social utilitarianism and human nature are analyzed. Finally, by delving into the two thinkers’ core viewpoints and their influence on modern philosophical discourse, the universality and uniqueness of Mencius' thought can be better understood. The results indicate that the concept of human nature being inherently good, advocated by Mencius, is the foundation for achieving social harmony, and his idea of harmony provides a new perspective for solving contemporary social problems, as well as important theoretical resources for modern ethics and political philosophy.